Improving Education Efficiency by Improving Student Retention (Comparing Students in The Field of Engineering with Economics In An Indonesian University) - Talar, Yulianti; Gozaly, Jimmy; Wirawan, Christina; Aprilia, Fiona (Jurnal Ilmiah Teknik Industri, 2023)
Universities play a vital role in human resource development. However, the dropout rate at many universities remains high that suffers education efficiency and effectiveness. This study examines factors that affect student retention to find a suitable approach. In this article, we compare engineering and economics students to see whether any variations in the characteristics impact student retention across these two fields. This knowledge sharpens ways to increase student retention rates. The research was conducted quantitatively using a questionnaire. Data were processed by discriminant analysis, crosstabulations, and descriptive statistical methods. The results found that different factors affect engineering and economics students’ retention. GPA and student satisfaction with close social relationships with fellow students were shown to be the determining variables for engineering students’ retention. Meanwhile, student satisfaction with lecturer feedback on course progress and student confidence to graduate on time are drivers of economics students’ retention.